[Lava Rock Near Hverfjall] - Streng, Evelyn Fiedler (1975)
Photograph of lava rock near Hverfjall. The grey, jagged rock covers the foreground dotted in green moss and foliage. Three people stand on the rock ground. A dark volcano sits in the top left corner of the photograph. The photograph is blurry.